Irregularities in the African ionosphere associated with total electron content anomalies observed during high solar activity levels - Anoruo, Chukwuma Moses; Rabiu, Babatunde; Okoh, Daniel; Okeke, Francisca Nneka; Okpala, Kingsley Chukwudi (Frontiers in Astronomy and Space Sciences, 2022)
In this paper, we investigate anomalies in total electron content (TEC) from 7 stations of the Africa Geodetic Reference Frame (AFREF) during the initial and recovery stages of the geomagnetic storm of 19 February 2014. Additionally, we study geomagnetic storms under the solar activity ascending period of March 2012 and low solar activity of May 2017 to emphasize scintillation effects, especially during the nighttime. We employ a 15-day median-average sliding window to study the latitudinal patterns of relative TEC (rTEC) and determine the storm ionospheric irregularities using the rate of TEC index (ROTI). The low-latitude stations show larger rTEC variations during the storm than the midlatitude stations. ROTI strength > 1 TECU/min is found at low latitude stations during postsunset and < 1 TECU/min at mid latitudes during daytime. The results from this study show that rTEC differences between midlatitude stations may be caused by dynamo of the electric field originating from energy input during geomagnetic disturbances. We observed a low latitude significant intensity of ionospheric irregularities and established that low latitude ionospheric irregularities are more pronounced during the storm initial and recovery stages.